2017
DOI: 10.6007/ijarbss/v7-i7/3094
|View full text |Cite
|
Sign up to set email alerts
|

Towards developing a framework on happiness and productivity among personnel in Institution of Higher Learning

Abstract: Happiness undeniably facilitates staff's productivity in the workplace. Productivity could be changed by the developments in the level of knowledge, income or the technology innovation. The focus of this paper is to ascertain the prospective factors that will influence the level of productivity among personnel in Institution in Higher Learning. Numerous factors were identified and it will be a useful input for future researchers that are seeking directions to investigate the contributing factors of productivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…According to a recent systematic review, happiness leads to greater career success (Walsh, Boehm, & Lyubomirsky, 2018), with others suggesting that the relationship between happiness and workplace attitudes and behaviors is causal (Layous, 2019). To provide specific examples, happy employees are associated with better performance (Bellet, De Neve, & Ward, 2020), greater productivity (Mazuki et al, 2017; Sgroi, 2015), increased sales (Gil, Kim, & Koo, 2017), task accuracy (Achor, 2011), and even higher stock prices (Cooper, 2012). Additionally, happy employees are related to improved customer satisfaction, higher peer evaluations, and are more likely to provide recommendations (Gil et al, 2017).…”
mentioning
confidence: 99%
“…According to a recent systematic review, happiness leads to greater career success (Walsh, Boehm, & Lyubomirsky, 2018), with others suggesting that the relationship between happiness and workplace attitudes and behaviors is causal (Layous, 2019). To provide specific examples, happy employees are associated with better performance (Bellet, De Neve, & Ward, 2020), greater productivity (Mazuki et al, 2017; Sgroi, 2015), increased sales (Gil, Kim, & Koo, 2017), task accuracy (Achor, 2011), and even higher stock prices (Cooper, 2012). Additionally, happy employees are related to improved customer satisfaction, higher peer evaluations, and are more likely to provide recommendations (Gil et al, 2017).…”
mentioning
confidence: 99%
“…Such new changes could influence the workload of academic and non-academic staff and the universities' management and culture. Mazuki et al (2017) have indicated that the requirement to enhance quality assurance and student support concerns the workload of academic staff, which also includes the struggles they face daily, for example, the large student to staff ratio. On the other hand, administrative staff's role has widened to a broader scope and an enhanced responsibility comprising quality assurance, provide support for teaching and research, finance and facility management, and master planning (Jung & Shin, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, for organizations, happiness of employees mean higher productivity and long-term positivity at the workplace. Happiness at work can possibility be influenced by many factors at work place, for example, career development, workload, infrastructure or salary (Mazuki et al, 2017). Quality of Life (QoL) is the aspect of life which can have psychological, physical and health-related meanings (Fallowfield, 1990).…”
Section: Introductionmentioning
confidence: 99%